Development of a Spectral Theory for Analysis of Non-Stationary Pulse Stochastic Electromagnetic Processes in Devices of Electric Transport Systems - Szeląg, Adam; Kostin, Mykola O.; Nikitenko, Anatolii; Mishchenko, Tetiana; Jefimowski, Włodzimierz (National Technical University of Ukraine "Igor Sikorsky Kiev Polytechnic Institute", Kiev, 2019)
ENG: A spectral analysis of traction voltages and currents is a basis for estimation of electromagnetic compatibility level and quality of consumed power in electric transport systems. However, such an analysis is usually performed for steady-state modes and only under the condition that the time realization of voltages and currents, being deterministic for continuous quantities, have infinite length. De facto, the electric transport devices operate in non-stationary dynamic modes (starting up, coasting, acceleration, iregenerative braking, stopping, wheel spin, voltage surges, etc.). As a result, the voltage across the traction motors and the current flowing through them are noncontinuous pulsed stochastic processes. It is necessary to add that in emergency modes the voltage and current are short-term single pulses.The paper presents the spectral analysis of such random sequences of pulses as well as their fronts and decays, the concepts of actual and instantaneousspectra. The analytical expressions for amplitudes and the initial phases of k-th harmonics are obtained using the discrete Fourier transformation. The numerical calculations of the spectral composition of stochastic pulse processes of voltage and current were performed for the DE1 and VL8 electric locomotives (Ukraine) as well as for trams operating on the i routes of the city of Dnipro. The actual and instantaneous spectra, as well as the spectra of the full correlation functions and their “tails”, were determined for the electric traction voltages and currents.
М. Kostin: ORCID 0000-0002-0856-6397; А. Nikitenko: ORCID 0000-0002-6426-5097; Т. Mishchenko: ORCID 0000-0001-6336-7350
Keywords: spectrum; electric transport; voltage; pulse; current; stochastic; instantaneous; correlation function; КТЕМ; КІСЕ